2017
DOI: 10.1038/srep40761
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen reduction of molybdenum oxide at room temperature

Abstract: The color changes in chemo- and photochromic MoO3 used in sensors and in organic photovoltaic (OPV) cells can be traced back to intercalated hydrogen atoms stemming either from gaseous hydrogen dissociated at catalytic surfaces or from photocatalytically split water. In applications, the reversibility of the process is of utmost importance, and deterioration of the layer functionality due to side reactions is a critical challenge. Using the membrane approach for high-pressure XPS, we are able to follow the hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
160
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(169 citation statements)
references
References 40 publications
8
160
0
1
Order By: Relevance
“…As the deposition Ar pressure increases, the shape of the grains remains needle-like but the size becomes relative larger and the surface becomes more porous. 43 The O 1s peak at 532.1 eV is a strong indication of the existence of OH group. Thus, the more porous the Mo film is, the more air it contains and the smaller the optical constants.…”
Section: Characterizations Of Mo Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…As the deposition Ar pressure increases, the shape of the grains remains needle-like but the size becomes relative larger and the surface becomes more porous. 43 The O 1s peak at 532.1 eV is a strong indication of the existence of OH group. Thus, the more porous the Mo film is, the more air it contains and the smaller the optical constants.…”
Section: Characterizations Of Mo Surfacesmentioning
confidence: 99%
“…The optical constants, including both the refractive index (n) and extinction coefficients (k), of Mo films for these three representative samples were also measured by spectral ellipsometry and the results are displayed in Figure 1D and E. From the effective medium approximation (EMA), the optical constants of a porous Mo film can be regarded as a weighted average of those of Mo and air atmosphere. 43,44 All the fitting parameters and the relative amount of each Mo and O species are presented in Table 1. The decreased refractive index and extinction coefficient with increased Ar pressure in the visible wavelength region indeed support the picture that an increasingly porous Mo surface is formed as the Ar pressure increases, in good agreement with the results of AFM images.…”
Section: Characterizations Of Mo Surfacesmentioning
confidence: 99%
“…It is interesting to note that intensity variation of MoHO4 − depending on different coating samples almost corresponds to the variation trend of MoO3 − . MoO3 shows catalytic activity and is known to interact with hydrogen, oxygen, For example, it was reported that HxMoO3 can be generated during the reduction process from MoO3 to MoO2 [33]. MoHO4 − was observed at a certain extent even for the DLC coating samples without hydrogen content; therefore, only hydrogen in DLC materials does not necessarily contribute to the MoHO4 − production.…”
Section: Tribofilm Compositions and Wear Behaviormentioning
confidence: 99%
“…[37][38][39] These bands support the formation of H 2 MoO 5 ·H 2 OQ Ds. [41] The deconvoluted O 1s peaks (Figure 3e)s uggest three types of bondingf or 530.5, 531.6, and 532.6 eV,c orresponding to Mo=O, MoÀOH, and MoÀperoxol inkages, respectively; [42] this confirms the formation of H 2 MoO 5 ·H 2 OQ Ds. [40] Furthermore, the chemical bonding environment of QDs has been evaluated by XPS.T he XPS survey spectrum of QDs ( ure S2 in the Supporting Information) reveals four distinct peaks at 231.7, 233,2 34.8, and 236.2 eV.T he peaks at 231.7 and 234.8 are assigned to the + 5o xidation state of molybdenum, corresponding to Mo 3d 5/2 and Mo 3d 3/2 electrons,r espectively.S imilarly,t he peaks at 233 and 236.2 eV are allocated to the + 6o xidation state, corresponding to Mo 3d 5/2 and Mo 3d 3/2 electrons, respectively.…”
Section: Reaction Mechanismmentioning
confidence: 77%
“…The SAED pattern ( bond vibrations, respectively. [41,42] The peak area ratio indicates the presence of as mall amount of the Mo 5 + (13.6 %) state with the Mo 6 + state;t he + 5o xidation state possibly arises from ah ydrogen insertion effect. The bands at ñ = 1179 and 1044 cm À1 indicate the presence of sulfate ions.…”
Section: Reaction Mechanismmentioning
confidence: 99%